Fauntleroy’s Letter to Quartermaster General 1852 - T. T. Fauntleroy (Symphony in the Flint Hills, 2013)
Letter to the Quartermaster General 1852 from T.T. Fauntleroy, colonel First Dragoons, concerning the economical point of view on repairing Fort Leavenworth for military operations and to propose a new location for a Fort.
Keywords: General; Quartermaster; Fauntleroy; army; military; Fort Leavenworth; Fort Riley; Kansas Territory; map; letter; land; pioneer; First Dragoons; routes; hunter; traders